Chemical composition and antifungal activity of Capsicum pepper aqueous extracts against plant pathogens and food spoilage fungi - Sepúlveda, Marcela; Costa, Jéssica; Cayún, Yasna; Gallardo, Víctor; Barría, Elsa; Rigotto Caruso, Glaucia; von Zeska Kress, Marcia Regina; Cornejo, Pablo; Santos, Cledir (Frontiers in Cellular and Infection Microbiology, 2024)
Capsicum pepper is a rich source of phytochemical compounds such as capsaicinoids, phenols, flavonoids, and so forth. Due to their antimicrobial and antioxidant potential all of these compounds have been assessed and used for both human and plant health benefits. Herein, three fresh varieties of Capsicum annuum (Cacho de Cabra, Bell pepper, and Hungarian Wax varieties) and one fresh and ripe variety of C. baccatum (Cristal) were evaluated. Capsaicin, dihydrocapsaicin, nordihydrocapsaicin and the phenolic content of Capsicum spp. extracts were characterised. The antifungal potential of capsaicinoids and antioxidant activities, and the ecotoxicity of each Capsicum spp. extract, using the model Galleria mellonella, were also evaluated. Phytochemical analyses showed that the Cristal and Hungarian Wax varieties presented the highest amount of capsaicin, dihydrocapsaicin, and nordihydrocapsaicin; while Bell Pepper had the highest phenol content and antioxidant activity. Capsaicinoids’ standards and Capsicum spp. extracts showed fungistatic activity against the fungal strains assessed. For the fungal strains assessed, the fungistatic activities of capsaicinoids’ standards were higher than those observed in Capsicum spp. extracts. The Hungarian Wax extracts inhibited slightly the growth of Aspergillus niger MUM05.11 and Fusarium oxysporum MUM16.143. Similarly, A. niger, F. oxysporum, Rhizopus arrhizus MUM16.05 and Alternaria sp. UFRO17.178 had their growth retarded by the use of Cacho de Cabra and Cristal extracts. Noticeable changes were observed in the fungal strains’ morphologies, such as the presence of fragile fungal structures, pigmentation loss, variation in the reproductive structures size and the conidia number. Capsicum extracts weaken the growth of fungi, indicating their fungistatic potential. Considering the fungistatic potential and non-ecotoxicity of these extracts, it is possible to suggest their use as a tool for pest management in the agri-food sector, controlling the growth and reproduction of fungi without posing a risk to non-target biodiversity.